Pulled In All Directions: Kindergarten Educator Challenges for Teaching Reading in Play-Based Programs - Messenger, Yvonne (Language and Literacy / Langue et littératie, 2024)
Kindergarten educators are experiencing tensions with pedagogical approaches for early literacy learning (Forgie et al., 2022; Pyle et al., 2018). They feel pressured to abandon play-based approaches in favour of direct instruction due to changes in provincial curriculum and school board policies (OHRC, 2022). This paper explores themes and responses by participants in a study with kindergarten educators during the first half of the 2023-24 school year. Challenges expressed included changing messages from school boards, a lack of clarity regarding direction, and the introduction of prescriptive programs. Suggestions of ways educators can build knowledge and agency through collaborative conversations are shared.